Architectural considerations for Hadoop applications : using clickstream analytics as an end-to-end example (O'Reilly Media, 2015)
"Implementing solutions with Apache Hadoop requires understanding notjust Hadoop, but a broad range of related projects in the Hadoopecosystem such as Hive, Pig, Oozie, Sqoop, and Flume. The good news isthat there's an abundance of materials - books, web sites,conferences, etc. - for gaining a deep understanding of Hadoop andthese related projects. The bad news is there's still a scarcity of information on how to integrate these components to implement completesolutions. In this video we'll walk through an end-to-end case studyof a clickstream analytics engine to provide a concrete example of howto architect and implement a complete solution with Hadoop."--Resource description page.